Regeneration of Speakers Of The Basiacuong Oral Tradition in Alam Panjang Village, Kampar Regency - Tiffany Yolanda; Siti Nurbayani; Wilodati (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Indonesia is a country rich in oral traditions. Oral traditions currently face serious challenges due to modernization and globalization. One oral tradition that still survives but faces the challenge of regeneration is Basiacuong, which is embodied in the Kampar Malay community. This study aims to analyze the regeneration process of Basiacuong oral tradition speakers in Alam Panjang Village, Kampar Regency. The study used a qualitative case study design. Data were collected through in-depth interviews, non-participant observation, and documentation studies. Data analysis was carried out through reduction, thematic categorization, narrative presentation, and triangulation of sources and techniques to maintain the validity of the findings. The results show that the regeneration of Basiacuong speakers in Alam Panjang Village is driven by the self-reliance of traditional leaders (niniok mamak) who built halls as routine training centers. The regeneration process takes place dialogically and gradually, with an emphasis on mastering the core structure (batang) before language ornamentation (bunga). This model creates an inclusive and consistent space for cultural reproduction. However, regeneration still tends to be reactive because the motivation to learn often arises after someone obtains a traditional title.